Telemedicine in Nursing Practice: Effectiveness and Challenges in Telehealth - Hutapea, Dwight Mahaputera Marulitua (Oshada, 2025)
Technological advancements in healthcare, particularly through telemedicine, have significantly changed nursing practice. Telemedicine allows nursing personnel to provide consultation, monitoring, and health education remotely, increasing the accessibility of services, and reducing the burden on health facilities. Studies show that telemedicine contributes to improved service efficiency and patient adherence to treatment. However, its implementation still faces challenges, especially in infrastructure readiness, regulations, and ethical and legal aspects. Barriers such as inequality in digital access, limitations in virtual clinical assessment, and digital literacy gaps also affect the effectiveness of this service. This study used a descriptive qualitative approach with thematic analysis method to explore the benefits and challenges of telemedicine in nursing. Data were obtained from 30 nurses experienced in telemedicine services through semi-structured interviews, participatory observation, and policy document analysis. The results showed that although telemedicine improves efficiency and access to health services, challenges such as communication reliability, patient data security, and nursing personnel welfare need further attention. Therefore, an adaptive strategy is needed that includes strengthening policies, developing equitable digital infrastructure, and training health workers so that telemedicine services can be implemented optimally, ethically, and sustainably.